2007
DOI: 10.1103/physrevlett.99.117205
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial Strain in the Hexagonal Plane of MnAs Thin Films: The Key to Stabilize Ferromagnetism to Higher Temperature

Abstract: The α − β magneto-structural phase transition in MnAs/GaAs(111) epilayers is investigated by elastic neutron scattering. The in-plane parameter of MnAs remains almost constant with temperature from 100 K to 420 K, following the thermal evolution of the GaAs substrate. This induces a temperature dependent biaxial strain that is responsible for an α − β phase coexistence and, more important, for the stabilization of the ferromagnetic α-phase at higher temperature than in bulk. We explain the premature appearance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…V. An alternative, but still nonperturbative and predominantly unbiased, approach would be the use of variational wave functions, either formulated generally or in the more specific projected wavefunction technique which leads to different types of flux phase. 67,68 Adapting this type of treatment to the coupled spin and orbital sectors without undue approximation remains a technical challenge.…”
Section: Kagome Latticementioning
confidence: 99%
“…V. An alternative, but still nonperturbative and predominantly unbiased, approach would be the use of variational wave functions, either formulated generally or in the more specific projected wavefunction technique which leads to different types of flux phase. 67,68 Adapting this type of treatment to the coupled spin and orbital sectors without undue approximation remains a technical challenge.…”
Section: Kagome Latticementioning
confidence: 99%
“…Such thin films in micron size or nanoscale are usually sputtered on silicon substrate to be compatible with the existing silicon integration technology. Because of the different thermal expansions or the lattice parameters of the film and substrate, prestress was usually induced during the fabrication [3]. Many experiments revealed that the stress played a crucial role in determining the properties of the materials [4].…”
Section: Introductionmentioning
confidence: 99%
“…The first-order magnetostructural phase transition temperature T t , at which the remnant magnetization becomes zero, can be enhanced either by applying an external magnetic field or by growing MnAs films on different oriented GaAs substrates [21]. For example, T t for MnAs films grown on GaAs (111)B is higher than that grown on GaAs (001) [18,22,23]. …”
Section: Introductionmentioning
confidence: 99%